A Legal Analysis of the Implications of Granting Mining Permits to Religious Organizations - Muhammad Nor; Sadino Sadino; Fokky Fuad (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2026)
Indonesia holds the world’s largest nickel reserves and accounts for approximately 40% of total global production. The management of mineral and coal mining is regulated under Law Number 4 of 2009 concerning Mineral and Coal Mining, which has subsequently been amended. Amid public opposition to the Job Creation Law, which has been criticized as unconstitutional and anti-democratic, the government sparked further controversy by issuing Government Regulation (GR) Number 25 of 2024, in connection with the revision of Law Number 3 of 2020 concerning Mineral and Coal Mining, which was subsequently enacted as Law Number 2 of 2025 through a plenary session of the House of Representatives of the Republic of Indonesia. GR Number 25 of 2024 amends GR Number 96 of 2021 concerning the Implementation of Mineral and Coal Mining Business Activities. This study aims to examine the consistency and harmonization of regulations governing mining permits and to analyze the implications of granting mining permits to community and religious organizations. This study employs normative legal research, focusing on the examination of statutory regulations and other legal sources. The analysis draws on formal legal sources, including laws, decisions, and regulations, which are grounded in prevailing societal norms and values. The primary legal source examined in this study is GR Number 25 of 2024 concerning the Implementation of Mineral and Coal Mining Business Activities. The study concludes that the issuance of mining permits, including those managed by community and religious organizations, must comply with the applicable regulatory framework. However, regulatory disharmony exists between Law Number 2 of 2025 and GR Number 25 of 2024, resulting in an inconsistency between the Government Regulation and the hierarchy of laws and regulations. Furthermore, granting mining permits to community and religious organizations may potentially result in financial losses to the state, given that such organizations lack the capacity and corporate experience required to manage mining operations.